The Role of Islamic Financial Literacy and Local Wisdom in Decisions to Use Sharia Banking Products: A Systematic Literature Review - Kaharuddin, Kaharuddin; Amrin, Amrin; Nurdin, Muhammad Riza; Sugiyarto, Sugiyarto; Su'ud, Su'ud; Supriyanto, Supriyanto (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2024)
This qualitative research aims to identify the role of Islamic financial literacy and local wisdom in using Sharia banking products. The study employs a qualitative method through a systematic literature review, sourcing data from credible journals with national and international indexes. The collected data is analyzed using the VOSviewer tool, which systematically maps trends and bibliometric networks and visualizes overlay maps and research density levels. The findings indicate that Islamic financial literacy and local wisdom significantly influence financial decisions to use Sharia banking products wherever these banks operate. In addition, local values have fundamental values that are integrated with the operational principles of Sharia banking so that it becomes a meeting point between Sharia banking and local wisdom that is owned by the community so that people in choosing Sharia banking products as a financial decision are not only driven by values. Sharia is also greatly influenced by culture.